Marriage, schooling, and excess mortality in prime-age adults: Evidence from South Africa - Yamauchi, Futoshi (International Food Policy Research Institute, 2008)
The institution of marriage plays a role in determining one’s risk of exposure to HIV. Since the transmission of HIV in the population is mainly through sexual activity, avoiding infection depends on risk-avoiding behavior. If the number of sexual partners is reduced after marriage, marriage may work as an institution to limit risks of HIV infection in society. This study undertook preliminary empirical assessment of recent panel data from South Africa. Results show that excess mortality is concentrated in unmarried adults aged 20–39 among both men and women (with a larger increase in mortality rate among women than men). Thus, the choice of when and who to marry appears to be related to risk of HIV exposure, leading to the authors to the primary question of this study; to determine the effect that schooling has on AIDS and excess mortality through changes in marriage behavior. This paper tests the hypothesis that schooling affects when one marries and thus impacts the risk of AIDS-related mortality.